Basics and fundamentals of the mechanisms of electrochemical reactors - dos Santos, Elisama V. [UNESP]; Cardozo, Jussara Câmara; Loor-Urgilés, Luis D.; Oliveira, Herbet L.; Gondim, Amanda D.; Cavalcanti, Lívia N.; Santos, José Eudes L. [UNESP]; Martínez-Huitle, Carlos A. [UNESP] (My University, 2024)
Nexus concept is the interconnection between the resource's energy, water, food, land, and climate. Interconnections between the Nexus sectors may benefit from climate change, energy demand, among others, to sustainable development goals (SDGs) through the integrated planning and management processes. Seventeen SDGs were established in several subject areas, such as water, energy, climate, oceans, urbanization, transport, science, and technology, to achieve it. At the same time, materials science has considerably contributed to the accomplishment of several SDGs, according to report maps of the most current sustainability initiatives and research within each SDG area. Advanced materials, for instance, may aid in achieving development objectives in key areas of focus on zero hunger, good health and well-being, clean water and sanitation, affordable and clean energy, industry, innovation and infrastructure, sustainable cities and communities, responsible consumption and production, climate action, and life below water. Then, the scientific and technological domains may develop and construct practical solutions in materials and their applications by identifying essential insights to open novel branches and landscapes for maximizing social benefits. Within this framework, innovative approaches to design and develop decontamination water technologies have been explored by electrochemistry, electrochemical engineering, and material sciences in themes that aim to increase environmental sustainability and Nexus interconnections. Electrochemical-driven processes have emerged as efficient and sustainable technologies for the detection and removal of pollutants in water matrices and wastes valorization, playing a key role in environmental protection, resources recovery, and climate neutrality, which could be simultaneously achieved when a Nexus applicability is visioned. This challenge is related to the lower production of wastes because of the direct use of electron as reagent, the improvements on the electrochemical transformations and, most importantly, because electrochemical processes can be powered with green energies or generate energy sources, contributing to a reduction in the carbon footprint of processes. Then, the integration of electrochemical approaches with materials science and reactors design toward the future of Nexus-technologies will be presented here, discussing the important features of main cell designs and their fundamental and electrochemical reactions.
Keywords: Batch cell; Electrochemical reactors; Flow cell; Materials; Wastewater treatment